Energy storages on the ferroelectric microstructures with transformation and nano vortex pattern - Han Zheng; Dongxu Pan; Zhengfa Li (Scientific Reports)
Abstract The energy storage and conversion in ferroelectrics can be realized through the microstructures of polar domains and domain walls, which resulting in the transformations from macro/microdomains to nanodomains or forming complex polar topologies. The physical basic models are adopted with domains and domain walls including 90o, 180o, 71o and 109o which are classified into two categories of 180o and α-angle, and are reconstructed with equivalent circuits simplified according to the reported patterns. Although electrical energy is known to be maintained by the charging capacitor, the energy storage effect on ferroelectric microstructure has been rarely explored for the relative paucity of experimental patterns reported with domains and domain walls. The diagrammatic sketches of transformation into nanodomain and vortex pattern are designed, and their respective formulas of total capacitances and energy densities are derived with crucial structural features. The findings reveal novel mechanisms of the relationship between energy storage and microstructures, that may be used to propose effective creation strategies or to design modern measure equipment in future.